Beyond popularity: A user perspective on observable behaviours in a digital platform. (29th August 2021) - Kunst, Katrine; Ringberg, Torsten; Vatrapu, Ravi
Abstract: The opinions and behaviours of others are recognised as powerful mechanisms for social influence in the digital sphere. The former, often referred to as electronic word of mouth (eWOM), is a thoroughly researched topic in the Information Systems literature. Conversely, the digital display of users' behaviours (e.g., number of past purchases) is less well understood despite the widespread adoption of this practice on digital platforms. Quantitative research has explored this interesting domain and found that observing others' behaviours entice observers to follow suit, but has left unaddressed the question of what sensemaking users derive from behavioural information. This is problematic as behavioural information is more open to interpretation compared to eWOM. In this article, we adopt the concept of electronic word of behaviour (eWOB) to denote such behavioural information. Through the lens of basic psychological needs theory and the qualitative means‐end chain approach, we expose how eWOB is interpreted and used by users of a digital platform, the music service Spotify. We find that eWOB leads to satisfaction of the basic psychological needs for relatedness and competence when observing others' behaviours. We also show how exposure to one's own past behaviours can yield a positive sense of self when presented in meaningful and private manners, but that it can also negatively impact users when their needs for autonomy and competence are not heeded by the digital platform. Finally, based on our empirical findings we offer a set of design implications for how digital platforms can optimise the use of eWOB.